Pengaruh Kesadaran Merek dan Citra Merek terhadap Minat Beli Produk Ramah Lingkungan: (Studi Kasus Konsumen Wardah Kolaka) - Zumarna Yani; Fitri Kumalasari; Almansyah Rundu Wonua (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine (1) the influence of Brand Awareness on Purchase Interest of Wardah Kolaka eco-friendly products, (2) the influence of Brand image on Purchase Interest of Wardah Kolaka eco-friendly products, (3) the influence of Brand Awareness on the Brand Image of Wardah Kolaka eco-friendly products. The influence of Brand Awareness on the Brand Image of Wardah kolaka's. The sample used was 110 respondents with the sampling technique used was purposive sampling. Analysis of research data using the Structural Equation Modeling (SEM-PLS) method. The results of this study show that Brand Awareness has a positive and significant effect on Buying Interest. This is evidenced by the t-count or t-statistic value of 4.580 greater than the t-table value of 0.338, and Brand Image has a positive and significant effect on Buying Interest, where the t-count or t-statistic value of 8.263 is greater than the t-table value of 0.533.